2022
DOI: 10.1017/jfm.2021.1113
|View full text |Cite
|
Sign up to set email alerts
|

Stable channel flow with spanwise heterogeneous surface temperature

Abstract: Recent studies have demonstrated that large secondary motions are excited by surface roughness with dominant spanwise length scales of the order of the flow's outer length scale. Inspired by this, we explore the effect of spanwise heterogeneous surface temperature in weakly to strongly stratified closed channel flow (at $Ri_\tau =120$ , 960; $Re_\tau = 180$ , 550) with direct numerical simulations. The configuration consists of equally sized strips of high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(43 citation statements)
references
References 67 publications
(175 reference statements)
6
37
0
Order By: Relevance
“…The two sets at Re τ = 180 are distinguished by their spanwise wavelengths λ y /h, namely π/4(≈ 0.79) and π/2(≈ 1.57). In our earlier study, we found that these heterogeneity lengths have the largest global impact on the flow (Bon & Meyers 2022). This is in agreement with a vast number of roughness studies showing that flow response to spanwise heterogeneous roughness is strongest for wavelengths of approximately 1 to 1.5 times the outer scale (e.g.…”
Section: Description Of Casessupporting
confidence: 90%
See 4 more Smart Citations
“…The two sets at Re τ = 180 are distinguished by their spanwise wavelengths λ y /h, namely π/4(≈ 0.79) and π/2(≈ 1.57). In our earlier study, we found that these heterogeneity lengths have the largest global impact on the flow (Bon & Meyers 2022). This is in agreement with a vast number of roughness studies showing that flow response to spanwise heterogeneous roughness is strongest for wavelengths of approximately 1 to 1.5 times the outer scale (e.g.…”
Section: Description Of Casessupporting
confidence: 90%
“…To make sure that our simulations with low and higher Reynolds number are comparable and both belong to the weakly stratified turbulent regime, all simulations have Ri τ = 120. This also enables easy comparison to cases from Bon & Meyers (2022) and allows to limit our parameter space.…”
Section: Description Of Casesmentioning
confidence: 99%
See 3 more Smart Citations